(untitled) (المجلة الدولية للبحوث العلمية, 2024)
The aim of this enquiry is to explore the delivery of influential graphic design content that is sensitive to the wants and needs of the target audience. By means of visual communication, how can the visions, aspirations, feelings and decision processes of the audience be stimulated so as to elicit more successful responses and subsequent interactions? The researcher has relied upon a descriptive analytical approach, based upon e-questionnaire answers from a sample of 41 Saudi Arabian designers, who provided 82% of the data statistics for this research, and 9 expatriate designers living in KSA, who contributed 18%. A theoretical framework that draws upon the existing literature concerning the concept of influential design content and its concepts in contemporary graphic design thought is proposed below. The results of this enquiry are used to develop a proposed strategy for effective design according to the above sustainable concepts, with the aim of embodying and enhancing the relevant cultural and design content. This exposition concludes by presenting the recommendations related to the linking of theoretical and applied concepts that emphasize the complementarity between them. Building an effective strategy that embodies sustainable professional values that contribute to achieving the concepts of influential design and its content is also recommended.